1998
DOI: 10.2337/diacare.21.7.1178
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness Indexes β of the Common Carotid and Femoral Arteries Are Associated With Insulin Resistance in NIDDM

Abstract: Arterial stiffness indexes beta of CCA and FA were associated with insulin resistance in NIDDM subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(131 citation statements)
references
References 0 publications
7
119
1
3
Order By: Relevance
“…7 Increased aortic PWV has been described by both Wahlqvist 26 and Lehman 27 in otherwise healthy subjects with type 2 diabetes. Salomaa 28 and Emoto 29 have also reported increased carotid artery stiffness in this patient group. Furthermore, in the ARIC study, carotid artery stiffness was positively correlated with serum glucose concentration.…”
Section: Arterial Stiffness and Type 2 Diabetes Mellitussupporting
confidence: 63%
“…7 Increased aortic PWV has been described by both Wahlqvist 26 and Lehman 27 in otherwise healthy subjects with type 2 diabetes. Salomaa 28 and Emoto 29 have also reported increased carotid artery stiffness in this patient group. Furthermore, in the ARIC study, carotid artery stiffness was positively correlated with serum glucose concentration.…”
Section: Arterial Stiffness and Type 2 Diabetes Mellitussupporting
confidence: 63%
“…In a study of 41 subjects a correlation between fasting glucose levels and local aortic distensibility was shown using a local invasive method 21 . In addition, one study using echo-tracking found an association between insulin resistance and femoral and carotid stiffness in patients with diabetes mellitus 22 . The proposed mechanisms of how 8 diabetes results in arterial stiffness are numerous and include for example formation of AGEproducts, as well as the influence of oxidative stress, monocyte vascular adhesion and inflammation on the arterial wall 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Although arterial stiffness has been examined in populations at increased risk for cardiovascular disease, including diabetes mellitus, 6 hypertension, 7 and postmenopausal women, 8 there are limited data exploring the hemodynamic characteristics of, specifically, premenopausal women and their risk for cardiovascular disease. Prior studies have examined the association of obesity and arterial stiffness in populations that included women from adolescence to older age.…”
Section: Introductionmentioning
confidence: 99%